Estimating the Need for Infiltration Wells to Support Groundwater Conservation and Surface Runoff Control in Enggal Subdistrict - Ayudia Hardiyani Kiranaratri (Green Publisher Indonesia, 2026)
Urban areas frequently encounter environmental challenges such as the reduction of green open spaces, water shortages during the dry season, and water ponding during the rainy season. These problems are mainly caused by rapid urbanization and the expansion of impervious surfaces, which reduce natural infiltration capacity and increase surface runoff. As a result, groundwater recharge decreases while the potential for urban flooding becomes higher. Similar conditions are observed in Enggal District, located in the central area of Bandar Lampung City, Indonesia. Therefore, effective stormwater management strategies are required to mitigate surface runoff while improving groundwater conservation. This study aims to estimate the required number of infiltration wells needed to achieve zero run-off conditions in Enggal District. The study area covered approximately 2.80 km² and consists of six urban villages with a population of 24,611 in 2025 based on the Enggal District Report. Land-use analysis indicates that the area has a surface runoff coefficient of 0.55. Hydrological analysis was conducted using 20 years of rainfall data (2005–2024) to determine rainfall characteristics and runoff potential. The rainfall intensity analysis for a 10-year return period produced a peak discharge of 15.88 m³/s with a rainfall intensity of 37.23 mm/h. Several designs with 2 scenarios were developed by considering variations in infiltration well dimensions and land availability within the study area.